The quality and equality of personal and professional development in teacher-artist partnerships - McGrarth, Vera (Education & Theatre, 2023)
Partnership implies equality. However, while earlier iterations of Teacher-Artist Partnership (TAP) failed to acknowledge teacher professionalism in their structure and implementation, more recent TAP evaluations tend to focus exclusively on teacher professional development. There is little in the way of documented evidence of artists’ development in TAP, let alone efforts to describe it. Case studies of two Irish I-TAP-PD residencies are presented below to illuminate the nature of the learning both professionals experienced through the I-TAP-PD process. The premise is to generate dialogue about the quality and equality of learning in TAP for both artists and teachers and prompt further research into this important area of enquiry. The case studies indicate that ongoing dialogue and practice between partners of equal status are key in generating real insight into children’s learning through the arts. And such insights have much to contribute to evolving TAP practices for the betterment of our arts-in-education provision for children in our schools.